Exosomes: the next frontier in vaccine development and delivery - Tan, Dan; Li, Guangyao; Fu, Wenyan; Lei, Changhai (Frontiers in Immunology, 2024)
Exosomes are small disk-shaped extracellular vesicles (EVs) that are naturally released into the environment by different types of cells. Exosomes range from 30-150 nm in size and contain complex RNA and proteins. They are widely found in body fluids such as blood, saliva, urine and breast milk and participate in cell communication by functioning as cell messengers. Almost all cell types can transmit information and exchange substances through the production and release of exosomes to regulate proliferation, differentiation, apoptosis, the immune response, inflammation, and other biological functions. Because exosomes exist widely in various body fluids, they are easy to obtain and detect and have the potential for use in disease diagnosis and prognosis detection. Exosomes can be genetically fused with targeted proteins, enhancing their biocompatibility and immunogenicity. Therefore, exosomes are the preferred vector tools for vaccines. In this review, we describe the characteristics of exosomes and discuss their unique and ambiguous functions in the immune microenvironment after infection. In this regard, we explored the ability of exosomes to carry immunogenic virus antigens and to establish adaptive immune responses. Exosomes can provide an interesting platform for antigen presentation and since vaccines are a powerful method for the prevention of infectious diseases, we further review the advantages and disadvantages of the use of exosomes in vaccine preparation. Overall, exosomes are emerging as a promising avenue for vaccine development.